International finance regulation : the quest for financial stability - Ugeux, Georges (Wiley, 2014)
"As the global market expands, the need for international regulation becomes urgentEffective financial regulation inspires market confidence, stability, consumer protection, and a reduction in financial crime. But over the past fifty years, a number of crises have arisen and spread around the world, making global regulation essentially impossible. The last crisis was endogenous due to internal flaws in the management and the structure of the financial system. While individual nations have reformed domestic regulation, these combined measures are still insufficient to prevent financial crisis. Comprehensive crisis prevention can only be initiated by strategic international regulation. International Finance Regulation: The Quest for Financial Stability focuses on the inspirations behind regulation, and examines the risks and consequences of fragmentation on a global scale. Author Georges Ugeux has four decades of experience in the legal and economic aspects of international finance. Formerly in charge of the NYSE and foreign stock exchanges, regulators, and governments, Ugeux is uniquely positioned to provide recommendations and suggestions from the perspective of a top global authority. In the book, he explores international regulation with topics such as: Laws, regulations, and the risks stemming from overregulation The transformation of the U.S. market and the creation of the Eurozone Development of a global framework and the inadequacy of the banking system In-depth examination of Basel III, the Dodd-Frank Act, Glass-Steagall Act, and the Volcker Rule The book also contains case studies from real-world scenarios like Lehman, CDS, Greece, the London Whale, and Libor to illustrate the concepts presented. Finance consistently operates within an increasingly global paradigm, and an overarching regulation scheme is becoming more and more necessary for sustainable growth. International Finance Regulation: The Quest for Financial Stability presents an argument for collaboration toward a comprehensive global regulation strategy to reach financial stability"--